Jurnalisme Profetik Di Era Society 5.0 : Analisis Korespondensi Kenabian bagi Aplikasi Dakwah - Amin Sihabuddin (Tabayyun: Journal of Journalism, 2022)
This paper is entitled "Prophetic Journalism in the Era of Society 5.0 Analysis of Prophetic Correspondence for Da'wah Applications". Focused problems. How is the da'wah application in the era of society 5.0.The study method uses a descriptive method, namely reading books that have a relationship with the problem. The theoretical foundation of “medium is the massage” by Marshal MC. Luhan. assuming that there are more and more variants of da'wah communication media in the digital era, prophetic journalism can utilize and make maximum use of modern media as a variant for communicating Islamic values ​​in preaching in order to apply the prophetic correspondence model. The letter stamp on every letter for state and tribal/qabilah officials is affixed with the Apostolic stamp as a form of accountability, apart from the completeness of administration and validity of a letter; as a source of news (source), while the content of the message (massage), prophetic journalism, invites worship only to Allah alone, with the principle of information. Honest, fair, responsible, tolerant and polite in reporting. The da'i application activities must make the content of the Prophet's correspondence a reference model in preaching through social media.